2016
DOI: 10.1177/1528083716679157
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of woven natural fiber fabric composites: Effect of weaving architecture, intra-ply hybridization and stacking sequence of fabrics

Abstract: A comprehensive analysis carried out on the mechanical and free vibration properties of woven natural fiber polymer composites is presented. Jute fabric with three different weave types (plain, basket and herringbone) and intra-ply woven jute-banana fabrics are considered for investigation of the effect of weave type of a fabric and its stacking sequence on mechanical, dynamic mechanical and free vibration properties. Enhancement of the properties is found with the number of layers of fabric and better propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 28 publications
3
32
0
1
Order By: Relevance
“…As different to above studies, Rajesh et al. 33 have investigated the effect of number of layers and stacking sequence on free vibration properties polyester matrix composites of woven jute, banana fabrics. Results show that vibration characteristics were best for four-layered composites compared to one-, two-, and three-layered composites.…”
Section: Stacking Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…As different to above studies, Rajesh et al. 33 have investigated the effect of number of layers and stacking sequence on free vibration properties polyester matrix composites of woven jute, banana fabrics. Results show that vibration characteristics were best for four-layered composites compared to one-, two-, and three-layered composites.…”
Section: Stacking Sequencementioning
confidence: 99%
“…Jute Arulmurugan et al, 29 Furtado et al, 30 Rajesh et al, 31 Rajesh et al, 32 Rajesh et al, 33 Rajesh et al, 34…”
Section: Polyestermentioning
confidence: 99%
“…Rajesh and Pitchaimani [13] discovered a stacking sequence to affect the flexural strength of two different layers of jute fibre, whereby a four-layer jute fibre is higher than three-layer jute fibre composite. Rajesh et al [14] studied the mechanical behaviour of woven natural fibre fabric composite, and indicated that a fourlayer plain weave fibre gave the highest mechanical performance as compared to one-layer, two-layer, and three-layer jute fibre. A study by Sathishkumar et al [15] found that the composite mechanical properties were increased by increasing the number of layers.…”
Section: Introductionmentioning
confidence: 99%
“…This treatment capable of increasing the surface roughness by removed a certain amount of cellulose, lignin, wax and oil content at the external fibre surface. The rough surface fibre is known to have better mechanical interlocking [13][14][15]. Alawar et al [19] who analysed the characteristics of treated date palm tree fibre revealed that treatment with 1% concentration NaOH for 1 h at 100°C was the ideal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the moulding process will alter the relatively regular structures due to the forced displacement of moulds. As is widely recognized, the properties of composites are directly decided by the microstructures [810]. In order to improve the accuracy of multiscale FE modelling of CFRP, the primary task is to establish geometric structures of representative domains as closer to realistic geometric characteristics as possible.…”
Section: Introductionmentioning
confidence: 99%